Artificial Intelligence (AI) Revolution in Accounting and Auditing Field: A Bibliometric Analysis - Sallem, Nur Raihana Mohd; Hussain, Nor Haliza Che; Muhmad, Siti Nasuha; Adnan, Nur Syuhada; Halmi, Syafiq Abdul Haris (Advances in Social Sciences Research Journal, 2024)
Artificial Intelligence (AI) integration in accounting and auditing is transforming these fields by enhancing efficiency, accuracy, and strategic decision-making. AI automates routine tasks, supports complex financial assessments, and improves fraud detection and audit processes. However, its implementation also raises ethical and regulatory concerns, such as data privacy and job displacement. Clear procedures and guidelines are essential to maintain internal stability and maximize AI’s value. This study aims to analyze the publication trends and citation metrics on AI in accounting and auditing while identifying the common research keywords in this area. It also identifies the main countries contributing research on this topic. The study is based on a bibliometric analysis of 105 articles from the Scopus database using the TITLE-ABS-KEY approach. In addition, the VOS Viewer software is used to create bibliometric networks and Harzing’s Publish or Perish software is used to assess the citation metrics of the articles. The analysis shows that the number of publications on AI in accounting and auditing is increasing, especially between 2020 and 2023. The articles were cited 1968 times, which corresponds to an average of 18.74 citations per article. The results show that the most common keywords discussed in this area are artificial intelligence, accounting, auditing, blockchain, and machine learning, which can be grouped into 7 clusters. The United States, China, the United Kingdom, and Saudi Arabia are among the countries that contribute to publications in this area. To summarize, this article provides important insights and publication trends into artificial intelligence in the area of accounting and auditing.